Challenges of Water Resources Governance under the Impact of Climate Change and Water Transfer - Atabak Jaffari; Ahmad Sharafati; Amin reza Neshat; Seyed abbas Hosseini (اکوهیدرولوژی)
Research Topic: The water resources management approach should be based on a water governance framework in different dimensions for optimal allocation in terms of time and space with a view to future conditions. Objective: Given the climatic stresses along with the lack of planning for water resource allocation, the approach of identifying future conditions is essential to understand the potential for development or development control. Method: In this study, considering the integrated exploitation of surface and groundwater resources in the Qazvin study area and the use of transferred water from Taleghan Dam, the inflow to this dam and the status of the aquifer under climate change conditions were simulated using two optimization algorithms, the Fire Falcon and the Emperor Penguin, using the LSTM model. In this study, two emission scenarios of SSP 126 and SSP 585 were evaluated as optimistic and pessimistic conditions using three climate models. Results: The results of the climate simulation showed that the amount of precipitation in the Qazvin study area will decrease and the temperature will increase. On the other hand, considering the selection of the LSTM-FHO model as the selected simulation model, the Qazvin aquifer was simulated in terms of groundwater level and the results indicated an increasing trend of decline and the aquifer deficit reaching more than 400 MCM. This deficit is also due to the decrease in the inflow to the Taleghan Dam. Conclusions: The results obtained in this study showed that the conditions of the Qazvin plain were not sustainable due to the limited water resources and the transfer of water flow from the Taleghan Dam, and these conditions indicated the lack of potential to meet the current situation and indicated the need to redefine the governance framework and water allocation in this plain.